Social Indicators in the "Health" Primary Goal Area of the OECD Social Indicators Development Programme. - Regan, Peter (My University, 1975)
Verf. zeigt mögliche Indikatoren des Gesundheitswesens, wie sie von der OECD vorgeschlagen werden.
Keywords: Gesundheit; Sozialindikator; Gesundheitswesen